Illegal organ trading: a comparative study in Malaysia, India and China / Erthania Waky … [et al.] - Waky, Erthania; Moh Bakery, Fawrah 'Aimi; Abdul Rahman, Hazim Syafiqah; Abdul Wahab, Izlaty (2010)
This research reviews a comparative study on illegal organ trading between Malaysia, China and India. The main focus of this research is to analyze the existing laws in Malaysia, China and India on the issue of illegal organ trading and to propose the reformation of the law in Malaysia regarding illegal organ trading. Data and information were gathered from interviews that had been conducted and from journal, articles, books and websites in the internet related to illegal organ trading. Firstly, this dissertation looks into the factors contributing to the crime of illegal organ trading in China and India. It also provides some reported cases in both countries pertaining to the issue as well as some suggested solutions. The research also includes scenarios from Malaysia and other countries at large. In the second part of this report, a discussion on the legal perspective pertaining to the issue of illegal organ trading in the three countries, namely Malaysia, China and India were conducted. This paper lays down some observations obtained from the study of the laws in the three countries such as the lacunae of the laws and whether the laws are effective in controlling the crime of illegal organ trading. The outcomes from the findings we obtained from various interviews conducted with the local organizations are provided in the final part of the report. A conclusion is made and recommendations are proposed based on the findings of the research with the expectation that Malaysia will take precautionary steps and reformations by either amending the existing laws or legislating a specific Act pertaining to illegal organ trading before it occurs in the future.